THE EFFECT OF SAVING HABITS ON THE FINANCIAL WELL-BEING OF EARLY CHILDHOOD AT SANGGAR BELAJAR AT-TANZIL CHERAS, MALAYSIA - Citra Putri Fauziah; M.Arif Rakhman; Sri Rahayu (LPPM UNIVERSITAS BINA INSAN, 2026)
Instilling early savings habits is vital for the future financial well-being of children from migrant worker families facing economic instability. However, research on early childhood financial well-being in nonformal education remains scarce. This associative quantitative study examines the effects of savings frequency, discipline, and motivation on the financial well-being of 35 students at Sanggar Belajar At-Tanzil Cheras, Malaysia, using total sampling. Data from questionnaires were analyzed via SmartPLS. The results reveal that only savings discipline significantly and positively impacts children's financial well-being, whereas frequency and motivation show no significant effect. This indicates that consistency and regularity matter more than how often or why they save. This study contributes to financial literacy frameworks for early childhood, particularly within the Indonesian migrant community in Malaysia.